How Does the Interplay Between Banking Performance, Digitalization, and Renewable Energy Consumption Shape Sustainable Development in European Union Countries? - Alina Georgiana Manta; Claudia Gherțescu; Roxana Maria Bădîrcea; Liviu Florin Manta; Jenica Popescu; Cătălin Valentin Mihai Lăpădat (Energies)
In the context of current global challenges, the integration of digitalization, financial performance, and renewable energy is pivotal in fostering sustainable and resilient economic development. The aim of this paper is to explore the interplay between banking performance, digitalization, and renewable energy consumption in the context of the European Union (EU), with a focus on sustainable economic development. This study examines the extent to which the digitalization and efficiency of the banking sector influence the uptake of renewable energy considering the EU’s environmental and economic priorities. The methodology used involves an econometric analysis based on statistical data from EU countries, using Fully Modified Ordinary Least Squares (FMOLS) to assess causal relationships between variables, complemented by Vector Autoregression (VAR) models and Granger causality tests to further investigate the dynamic interactions among the variables. The data were analyzed to examine the correlation between banking performance, digitalization, and renewable energy consumption levels. The results reveal a positive correlation between greater digitalization in the banking sector, stronger financial performance, and higher investments in renewable energy sources. These factors also support the transition to a green economy, but the effect varies between EU countries depending on national policies and existing digital infrastructure. Recommendations for policymakers include stimulating digitalization in the financial sector, creating a regulatory framework to encourage green energy investments, and strengthening collaboration between financial institutions and the energy sector to facilitate the transition to renewables. This paper also suggests a fiscal policy conducive to technological innovation and digitalization to accelerate the uptake of renewable energy.